Pengaruh Kebisingan terhadap Konsentrasi Belajar dengan Penerapan Fitur Active Noise Cancelling pada Siswa Privat CV. Prima Aksara - Komang Gede Agus Diva Wiguna, I; Gusti Ngurah Priambadi, I; Made Dwi Budiana Penindra, I (Journal of Comprehensive Science, 2025)
This research examines the effect of noise on the learning concentration of private students at CV. Prima Aksara and the effectiveness of the Active Noise Canceling (ANC) feature in reducing the impact of noise. The method used is an experimental study with a quantitative approach, involving measuring noise levels using a Sound Level Meter and evaluating student concentration through questionnaires before and after using ANC. The results showed that noise had a significant negative impact on students' learning concentration, with the majority of students having difficulty focusing in noisy environments. After implementing ANC, there was a significant increase in learning concentration and a decrease in detected noise. Statistical analysis through the Chi-Square and McNemar tests supports that ANC is effective in improving a more conducive learning environment. Thus, the use of ANC technology can be a solution in overcoming noise disturbances in educational environments.